THE IMPACT OF BLOCKCHAIN-BITCOIN IN MALAYSIAN MARKETS - Miraz, Mahadi Hasan; Hye, A. K. Mahbubul; Habib, Md. Mamun (International Journal of Supply Chain Management, 2019)
In the field of technological advance, when everyone talks about "the Internet of thingsâ?, and so it is expected that there is something and everything in the relationship, money should not be left. The currency of the papers is a thing of the past, since the virtual currencies are beginning to take control and Bitcoin is ready to achieve this performance. Not only does it revolutionize the way it is paid, but it also potentially affects the USD as the USD, which is already a challenge for the challenges of the EURO or the Chinese Renminbi Yuan (CNY). The increase in crypto currencies will give a new dimension to this challenge for the Ringgit (MYR) in Malaysia. The purpose of this study is to understand the many factors that are gaining momentum in Bitcoin (BTC) in several areas of global finance and how confusing it can be, including the financial system of the major fiduciary currencies, which is mainly MYRs. The most important variables examined are Bitcoin, Bitcoin Technology, Bitcoin Economy and Bitcoin as currency. Furthermore, the study would propose a framework that would become the foundation for the furthering of upcoming explorations. Finally, this study would act as a stepping ground for making effective contributions towards understanding the best possible way to plan for the success of retail market in Malaysia.